Etika dan Inovasi GenAI: Perspektif Mahasiswa Program Studi Bimbingan dan Konseling Terhadap Peran Konselor - Setiawan, Muhammad Andri; Makaria, Eklys Cheseda; Maulana, Muhammad; Suriansyah, Ahmad; Aslamiah, Aslamiah (Jurnal Ilmiah Global Education, 2025)
This study aimed to examine the perceptions of Guidance and Counseling students on the ethics and innovation of Generative Artificial Intelligence (GenAI) and its influence on the future counselor’s role. A quantitative descriptive approach was employed using a survey method with a Likert scale. A total of 134 students across three cohorts (2022, 2023, and 2024) participated in this study. The results showed that the 2024 cohort demonstrated a higher tendency to use GenAI and perceived it as a positive innovation, while the 2022 and 2023 cohorts showed greater ethical awareness in using the technology. This indicates a gap between technological proficiency and ethical sensitivity among students. The study concluded that GenAI offers potential benefits for academic innovation but must be balanced with ethical considerations to preserve the integrity of the guidance and counseling profession. These findings highlight the importance of integrating digital ethics into the educational curriculum for prospective counselors.